2020
DOI: 10.24831/jai.v48i1.27597
|View full text |Cite
|
Sign up to set email alerts
|

Produksi Kacang Tunggak (Vigna unguiculata [L.] Walp) dengan Input Pupuk Rendah

Abstract: Cowpea is prospective as a substitute for soybeans, as raw material for tempeh. In this study, low inputs of cowpea production is proposed. This study aimed to determine the effect of manure and nitrogen fertilizer on the growth and production of cowpea. The study was conducted at the Cikabayan Experimental Station, IPB, Bogor, Indonesia, from November 2018 to March 2019, using a split-plot design. As the main plot was goat manure rates consisted of 0, 2.5, and 5 tons ha-1. The subplots consisted of four rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The pods were harvested at intervals of 5 days for each harvest period. Early harvesting is suspected to be due to the influence of irrigation volume on cowpea, this is not following the results of research by Fadillah et al (2020) that cowpeas are harvested at the age of 59-81 days after planting.…”
Section: Yield and Yield Componentmentioning
confidence: 86%
See 1 more Smart Citation
“…The pods were harvested at intervals of 5 days for each harvest period. Early harvesting is suspected to be due to the influence of irrigation volume on cowpea, this is not following the results of research by Fadillah et al (2020) that cowpeas are harvested at the age of 59-81 days after planting.…”
Section: Yield and Yield Componentmentioning
confidence: 86%
“…This is presumably because the plants during the early flowering period need more water than those during the late. The greater the number of flowers, the higher the seed weight produced per plant (Fadillah et al, 2020). The research results on 20 varieties of soybean plants showed that the number of flowers correlated with the number of filled pods produced per plant and the number of pods correlated with seed weight per plant (Suyamto & Musalamah, 2016).…”
Section: Reproductive Charactersmentioning
confidence: 97%
“…The presence of minerals in cowpea is utilized by molds as nutrients to grow so that it has good cohesiveness. Optimal metabolism is indicated by the compactness of the mycelium due to the activity of Rhizopus oligosporus (Fadillah et al, 2020). The results of ash content analysis of cowpea seeds and cowpea tempeh with fermentation duration (35 hours, 45 and 54 hours) can be seen in Table 1.…”
Section: Ash Contentmentioning
confidence: 99%
“…Another study showed that 100 g of mature cowpea seeds contain protein 22 g; fat 1.4 g; carbohydrates 51 g; water 10 g; vitamins 3.7 g; carbon 3.7 g; calcium 104 mg and other nutrients. The energy produced is 1420 kj/100 g or 339 kcal/100 g (Fadillah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The potential yield of cowpea seeds is quite high, reach 1.5-2 tons/ha, depends on the variety, location, growing season and cultivation applied. In addition, cowpeas can be grown with manure and low nitrogen [7].…”
Section: Introductionmentioning
confidence: 99%